Incidence of herpes simplex virus type 2 in young reproductive age women in Mysore, India - Purnima Madhivanan; Yea-Hung Chen; Karl Krupp; Anjali Arun; Jeffrey D Klausner; Arthur L Reingold (Wolters Kluwer Medknow Publications, 2011)
Context: There are sparse data on herpes simplex virus type 2 (HSV-2) infection in India. HSV-2 is one of the most common sexually transmitted infections and the primary cause of genital ulcer disease worldwide. Aim: The aim of this study is to describe the incidence of HSV-2 infection among young reproductive age women in Mysore, India. Setting and Design: Between October 2005 and April 2006, 898 women were enrolled into a prospective cohort study in Mysore, India, and followed quarterly for 6 months. Materials and Methods: An interviewer administered questionnaire was used to collect demographic and social risk factors, and physical examination was conducted for collection of biological specimens to screen for reproductive tract infections at each visit. Serologic testing was conducted for the presence of HSV-2 antibodies using HerpeSelect HSV-2 enzyme-linked immunosorbent assay. Statistical Analysis Used: Data were analyzed using R. Incidence density rates were calculated using Poisson distributions with person-time of follow-up as denominator. Person-time was calculated as time from enrollment until time of first positive HSV-2 test. Results: There were 107 women with HSV-2 antibodies leaving 700 women with negative results at enrollment. The analysis included 696 out of which, there were 36 HSV-2 seroconversions during the study period. The study cohort accumulated roughly 348 woman-years of follow-up, yielding an HSV-2 acquisition rate of 10.4 cases/100 woman-years. All detected infections were asymptomatic. Conclusions: HSV-2 incidence is moderate in this community sample of young reproductive age monogamous women. More research is needed to establish incidence estimates in different Indian settings.